A comparison of productivity in the Federal Republic of Germany, Japan and the USA - Gundolf F. Hecker (Intereconomics, 1982)
The rise in unemployment is often blamed not only on the slowdown in economic growth but also on the increasing pressure to rationalise. Greater rationalisation should, however, have led to an increase in labour productivity, but this has not happened in the Federal Republic of Germany nor in a series of other major industrial countries. Instead, there has been a marked slowdown in the rate of productivity advance. Why is this, and what is the outlook for the future?
Keywords: 330; Productivity